2011
DOI: 10.1590/s1415-47572011005000053
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms associated with the risk of lung cancer in a healthy Mexican Mestizo population: application of the additive model for cancer

Abstract: Lung cancer is the leading cause of cancer mortality in Mexico and worldwide. In the past decade, there has been an increase in the number of lung cancer cases in young people, which suggests an important role for genetic background in the etiology of this disease. In this study, we genetically characterized 16 polymorphisms in 12 low penetrance genes (AhR, CYP1A1, CYP2E1, EPHX1, GSTM1, GSTT1, GSTPI, XRCC1, ERCC2, MGMT, CCND1 and TP53) in 382 healthy Mexican Mestizos as the first step in elucidating the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The genotype distributions for GSTM1, GSTT1, and GSTP1 polymorphisms in control subjects were in agreement with the results of previous reports in Mexicans subjects (Pérez-Morales et al, 2011;Martínez-Rodríguez et al, 2013). The frequency of the GSTM1 null genotype found in this study was 30%, which is similar to the values observed in Asians and African Americans (~27%), but not similar to the value in Caucasians (~50%).…”
Section: Discussionsupporting
confidence: 92%
“…The genotype distributions for GSTM1, GSTT1, and GSTP1 polymorphisms in control subjects were in agreement with the results of previous reports in Mexicans subjects (Pérez-Morales et al, 2011;Martínez-Rodríguez et al, 2013). The frequency of the GSTM1 null genotype found in this study was 30%, which is similar to the values observed in Asians and African Americans (~27%), but not similar to the value in Caucasians (~50%).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we observed similar null GSTM1 genotype frequencies in our control group at those that had been previously reported in Mexico (Pérez-Morales et al, 2011;Martínez-Ramírez et al, 2013;Sandoval-Carrillo et al, 2014). The genotypic GSTM1 null frequencies were 38 and 45% in the control group and in patients with BC, respectively, suggesting an association of this allele as a risk factor in BC.…”
Section: Discussionsupporting
confidence: 92%
“…Several reports in the general Mexican population have described a high frequency of the null GSTM1 allele of approximately of 37-44%, depending on the tested region (Pérez-Morales et al 2011;Martinez-Ramirez et al, 2013;Sandoval-Carrillo et al, 2014). However, there are no descriptions to date of an association of the null GSTM1 polymorphism with BC in Mexican women.…”
Section: Introductionmentioning
confidence: 99%
“…Restriction fragment length polymorphism (RFLP) analysis for CYP1A1 rs1048943, CYP1B1 rs1056836, COMT rs4680 and GSTPI rs1695 was performed as previously described [19].…”
Section: Genotypingmentioning
confidence: 99%